Book of Abstracts of the First International Conference - Building Bridges in STEAM Education in the 21st Century - Soares, Filomena Baptista (2022)
The International Conference BBC'22 aims to provide an opportunity for all academic and non-academics to share their personal experiences and projects, presenting their contributions and getting feedback from other attendees.